An updated meta-analysis approach for genetic linkage - Etzel, Carol J (BioMed Central, 2005)
We present a meta-analysis procedure for genome-wide linkage studies (MAGS). The MAGS procedure combines genome-wide linkage results across studies with possibly distinct marker maps. We applied the MAGS procedure to the simulated data from the Genetic Analysis Workshop 14 in order to investigate power to detect linkage to disease genes and power to detect linkage to disease modifier genes while controlling for type I error. We analyzed all 100 replicates of the four simulated studies for chromosomes 1 (disease gene), 2 (modifier gene), 3 (disease gene), 4 (no disease gene), 5 (disease gene), and 10 (modifier gene) with knowledge of the simulated disease gene locations. We found that the procedure correctly identified the disease loci on chromosomes 1, 3, and 5 and did not erroneously identify a linkage signal on chromosome 4. The MAGS procedure provided little to no evidence of linkage to the disease modifier genes on chromosomes 2 and 10.